Dietary docosahexaenoic acid reduces fat deposition and alleviates liver damage induced by D-galactosamine and lipopolysaccharides in Nile tilapia (Oreochromis niloticus) - Liu, Yi-Chan; Limbu, Samwel Mchele; Wang, Jin-Gang; Wang, Mai; Chen, Li-Qiao; Qiao, Fang; Luo, Yuan; Zhang, Mei-Ling; Du, Zhen-Yu (Comparative biochemistry and physiology. Toxicology & pharmacology, 2023)
Liver health is important to maintain survival and growth of fish. Currently, the role of dietary docosahexaenoic acid (DHA) in improving fish liver health is largely unknown. This study investigated the role of DHA supplementation in fat deposition and liver damage caused by D-galactosamine (D-GalN) and lipopolysaccharides (LPS) in Nile tilapia (Oreochromis niloticus). Four diets were formulated as control diet (Con), Con supplemented with 1 % DHA, 2 % DHA and 4 % DHA diets, respectively. The diets were fed to 25 Nile tilapia (2.0 ± 0.1 g, average initial weight) in triplicates for four weeks. After the four weeks, 20 fish in each treatment were randomly selected and injected with a mixture of 500 mg D-GalN and 10 μL LPS per mL to induce acute liver injury. The results showed that the Nile tilapia fed on DHA diets decreased visceral somatic index, liver lipid content and serum and liver triglyceride concentrations than those fed on the Con diet. Moreover, after D-GalN/LPS injection, the fish fed on DHA diets decreased alanine aminotransferase and aspartate transaminase activities in the serum. The results of liver qPCR and transcriptomics assays together showed that the DHA diets feeding improved liver health by downregulating the expression of the genes related to toll-like receptor 4 (TLR4) signaling pathway, inflammation and apoptosis. This study indicates that DHA supplementation in Nile tilapia alleviates the liver damage caused by D-GalN/LPS through increasing lipid catabolism, decreasing lipogenesis, TLR4 signaling pathway, inflammation, and apoptosis. Our study provides novel knowledge on the role of DHA in improving liver health in cultured aquatic animals for sustainable aquaculture. [Display omitted] •Dietary DHA alleviates liver fat deposition in Nile tilapia.•Dietary DHA alleviates liver damage induced by D-GalN/LPS in Nile tilapia.•DHA regulates TLR4 signaling pathway, inflammation and apoptosis in Nile tilapia.